ANALISIS VISUAL STORYTELLING PADA POSTER FILM “BUMI MANUSIA” - Satriadi, Satriadi; Adinda, Shafa (Universitas Negeri Makassar, 2023)
Film posters are important aspects of visual communication since they serve not only as a commercial tool but also as a medium full of significance, particularly in the film